Entrepreneurial intention (EI) among undergraduate students in International Islamic University Malaysia (IIUM): empirical evidence - Muhammad, Aliyu Dahiru; Haneef, Mohamed Aslam; Abubakar, Isa Ado (INSI Publications, 2013)
Recently, entrepreneurship receives most attention than ever before. The importance of inculcating entrepreneurship education among young and fresh graduates cannot be over stressed. Similarly, studies show that student who participates in entrepreneurship program is more willing to start his own business than a student who does not undergo any of these programs. The recent financial crisis serves as lessons for employees and potential graduates that should no longer rely on big companies. The objective of this paper is to investigate the factors that determine entrepreneurship intentions among University students. The paper employed Theory of Planned Behavior (TPB), to examine the students` intentions to start up small scale businesses. Based on the sample size of 222, it was found that power of behavioral control and personal attitude are the major determinants to start up. Other interesting findings revealed in the study were the mediating roles of personal attitude and power of behavioral control. The research utilizes Structural Equation Modeling (SEM) in the analysis and Amos software version 18 to test the hypotheses.